Effect of solution treatment and aging on microstructure and tensile properties of high strength β titanium alloy, Ti–5Al–5V–5Mo–3Cr. (5th February 2015) - Shekhar, Shashi; Sarkar, Rajdeep; Kar, Sujoy Kumar; Bhattacharjee, Amit
Highlights: Alloy was double melted in vacuum arc and then it was thermo-mechanically processed. Microstructure was determined as a function of solution treatment and aging (STA). Tensile properties were determined as function of β and α + β STA. β STA resulted in higher strength in compared to α + β STA. α + β STA resulted in optimum condition strength and ductility. Abstract: Ti–5Al–5V–5Mo–3Cr is one of the latest high strength β titanium alloys to be used for larger size components in aircraft structures replacing Ti–10V–2Fe–3Al. In the present study, a double VAR melted ingot was thermo-mechanically processed and it's microstructure and tensile properties determined as a function of β as well as α + β solution treatment and aging. The β solution treatment and aging resulted in higher strength and α + β solution treatment and aging resulted in an optimum combination of strength and ductility. Its aging behavior was studied as a function of time and temperature and corresponding microstructure as well as fractographs of tensile tested specimens were recorded. This systematic study should help in further modeling its mechanical behavior.